Aortic Valve Replacement with Single-Strip Autologous Pericardium - Dilawar, Ismail; Rachmat, Jusuf; Puruhito, Ito; Alwi, Idrus; Sastroasmoro, Sudigdo; Suhendro, Suhendro; Liem, Isabella Kurnia; Siagian, Minarma; Jusuf, Ahmad Aulia; Makdinata, William; Taslim, Imamurahman; Melisa, Stefanie (The Thoracic and Cardiovascular Surgeon, 2023)
Background Aortic valve replacement with mechanical valves is the standard treatment for aortic valve disease in Indonesia. Its usage is associated with high cost, risk of endocarditis and thromboembolic event, and lifetime consumption of anticoagulants. We performed a novel replacement technique of the aortic valve using an autologous pericardium and evaluated the short-term outcomes.Methods From April 2017 to April 2020, 16 patients underwent aortic valve replacement with a single-strip autologous pericardium. Outcomes of the left ventricular reverse remodeling (LVRR), 6-minute walk test (6MWT), and soluble suppression of tumorigenicity-2 (sST-2) were measured at 6 months postoperation.Results A total of 16 surgeries were performed using aortic valve replacement with single-strip pericardium without conversion to mechanical valve replacement. The patients included eight males and eight females, and the mean age was 49.63 ± 12.54 years. The most common diagnosis was mixed aortic valve stenosis and regurgitation (9 cases). Five patients underwent a concomitant coronary artery bypass graft (CABG) procedure and 12 patients underwent either mitral or tricuspid valve repair. The mean aortic cross-clamp time was 139.88 ± 23.21 minutes and cardiopulmonary bypass time was 174.37 ± 33.53 minutes. At 6 months postoperation, there was an increase in the distance walked at the 6MWT (p = 0.006) and a decrease of the sST-2 level (p = 0.098). Echocardiogram showed two patients had LVRR. Survival and freedom from reoperation are 100% at 1 year of follow-up.Conclusion Aortic valve replacement with a single strip of pericardium is a good alternative to aortic valve replacement with a mechanical valve. Short-term evaluation at 6 months postoperation showed improvement in clinical status and echocardiographic parameters compared to baseline.
Keywords: aortic valve replacement; single-strip pericardium; left ventricle reverse remodeling; six minutes walking test; soluble suppression of tumorigenicity-2